NOTE ON THE LOCOMOTORY BEHAVIOUR OF THE MUDSKIPPER BOLEOPHTHALMUS BODDARTI - De, J K; Nandi, N C (Indian Journal of Fisheries, 2011)
Boleophthalmus bpddarti, besides swimming, displays four modes of locomotion, viz., crutching, skipping, skimming and climbing. Locomotion by crutching is to acquire fixxl, skipping and skimming to escape and climbing to rest. Significance of such locomotory behaviours has been outlined.